Answer:
So you are going to use the distributive property with what is inside the parenthesis.
2x + 3y + 2(x - y) - 3
You are going to distribute the 2 to the x and then 2 to the y. You need to pay attention to the signs that are out in front of the coefficients, or variables that you are using.
So it's 2*x = 2x and 2*y = 2y.
2x + 3y + 2x - 2y - 3
Then you can combine like terms
2x + 3y + 2x - 2y - 3
So combine all of your x's together 2x + 2x = 4x
Then combine all of your y's together 3y - 2y = y
So your final answer is
4x + y - 3